Dukungan Keluarga dan Penerapan Self Care Management Lansia Penderita Hipertensi - Yulita Meo, Maria; Pati Rangga, Yohanes Paulus; Ovi, Fransiska (STIKES Ngesti Waluyo, 2023)
Hypertension is the first cause of death in the world. Handling of hypertension includes pharmacological and non-pharmacological therapy such as self-care management. Self-care management is defined as a person's activities in controlling symptoms, carrying out physical and psychological treatment or adjusting lifestyle with the disease experienced in order to maintain health and well-being. The aim of the study was to analyze the correlation between family support and the application of self-care management for elderly people with hypertension in the working area of ​​the Nita Health Center. This is a quantitative research with a correlational analytic design. The sampling technique used was Accidental sampling with a sample size of 65 people. Questionnaires are used as research instruments. Bivariate analysis using the Spearman Rank test. The results showed that 40 people (61.5%) had adequate family support, 13 people (20.1%) lacked of family support, and 12 people (18.4%) had good family support. There were 12 people (18%) with good self-management, 7 people (11%) had enough self-management, and 46 people (71%) with less self-management. The results of the Spearman Rank statistical test showed a significant value of p = 0.257, therefore H0 was accepted, Ha was rejected. It means that family support has no relationship with self-care management for elderly people with hypertension in the working area of ​​the Nita Health Center.